2020
DOI: 10.47108/jidhealth.vol3.iss1.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of internal displacement on psychosocial and health status of students residing in the hostel of Anbar University, Iraq

Abstract: Background: Displacement in Iraq has been widespread and for frequent periods. Education was one of the most prominent victims of displacement at all levels, including higher education. This study aims to assess the impact of displacement on the psychosocial and health status of undergraduate students living in student accommodation of Anbar University, Iraq.    Methods: A retrospective cross-sectional study was conducted from 3rd to 17th April 2017. Data was collected using a universal sampling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, the respondents rated the satisfaction moderate to a high level. In contrast, our respondents belong to the central and western regions, subjected to successive waves of armed violence, and forced displacement, with insecurity and lack of services [15,16,37].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the respondents rated the satisfaction moderate to a high level. In contrast, our respondents belong to the central and western regions, subjected to successive waves of armed violence, and forced displacement, with insecurity and lack of services [15,16,37].…”
Section: Discussionmentioning
confidence: 93%
“…The lack of medical services in the countryside may be considered one of the main weaknesses in managing the security, services, and reconstruction files in conflict-affected areas. Ali jadoo et al [15] and Al-Samarrai et al [16] found that most of the IDPs have refused to return to their homes due to the security situation and lack of services.…”
Section: Discussionmentioning
confidence: 99%
“…More than onethird (35.9%) of our sample browse the Internet and 28.2% use smartphones for social media. In a similar situation to the COVID-19 quarantine, a previously conducted study in Iraq among internally displaced people showed that 29.3% of university students used smartphones for social media as alternatives to their previous social life [40]. Saadeh et al [27] found that about 85.0% of 6,157 surveyed undergraduate students in Jourdan had "increased or greatly increased" the usage of smartphones during the COVID-19-related quarantine.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies published over the past two decades have extensively discussed what is happening in Iraq. Nevertheless, we can sum up the goals of the invasion of Iraq in bringing down the modern Iraqi state and replace it with sectarian parties and militias; destroying most of the Iraqi infrastructure and making it a target for systematic looting and sabotage; creating an environment for unprecedented administrative and financial corruption; tearing apart the societal fabric and pushing towards the sectarian tension and internal fighting, as it happened in the fabricated sectarian war in 2006 and allowing terrorist organizations to invade Iraq such as the Islamic State in Iraq and Syria (ISIS) when storming most of the central and western parts in mid-2014 [6,[11][12]. Unfortunately, the health sector has had its share of destruction.…”
Section: Health System In Iraqmentioning
confidence: 99%